Protective effect of melatonin on water avoidance stress induced degeneration of the bladder - ERCAN, FERİHA; ŞENER, GÖKSEL (ELSEVIER SCIENCE INC, 2005)
Purpose: The role of melatonin on chronic water avoidance stress (WAS) induced degeneration of bladder epithelium (urothelium) was investigated. Materials and Methods: Wistar albino rats were exposed to WAS for 2 hours daily for 5 days (WAS group). Before exposing them to WAS 10 mg/kg melatonin (WAS plus melatonin group) was injected intraperitoneally into the animals. Bladder samples were investigated with light and electron microscopy. Lipid peroxidation. and glutathione levels were also measured in the bladder. Results: In the WAS only group an increased number of mast cells in the mucosa, ulcerated areas, vacuole formation and dilated perinuclear cisternae, and dilatation in the intercellular spaces in the urothelium were observed. In the WAS plus melatonin group relatively normal urothelial topography, a decreased number of mast cells in the mucosa, some dilatation between intercellular areas, regular perinuclear cisternae and tight junctions were observed. Increased lipid peroxidation and decreased glutatione levels in WAS rats were reversed by melatonin. Conclusions: The results show that melatonin reverses WAS induced degenerative changes in the bladder.
Keywords: bladder; rats; Wistar; cystitis; interstitial; melatonin; EPITHELIAL PERMEABILITY BARRIER; INTERSTITIAL CYSTITIS; SURFACE GLYCOSAMINOGLYCANS; MAST-CELLS; ACTIVATION